MENERAWANG PROBLEMATIKA KEBIJAKAN INVESTASI NEGARA GUNA MENGKRITISI UNDANG-UNDANG NO.25 TAHUN 2007 TENTANG PENANAMAN MODAL - Endang Sutrisno (Hukum Responsif, 2012)
The development of the legal order in a global era has led the legal to cross-domain border on another level. Law must be able to be the order of primacy to construct values of justice, predictability and usability. Legal policy through legislation products often respond to national interests. It should have a balance of interests between national and global. The content of Act 25 of 2007 on Investment should reflect these problems. In fact, in the level of implementation, it is not able to accommodate a balance of interests. A dichotomy of interests due to the inclusion of global values causes the negation of national interest. Key Words : Legal Order; National Interest & Global Interest